Peran Brand Image dalam Memediasi Pengaruh Celebrity Endorser, Product Quality, Social Media Marketing, dan Credibility of Influencer terhadap Purchase Intention - Arif Hadi Prasetyo; Arif Budiharjo; Noor Rosyadi; Anis Setyorini (Jurnal Pemimpin Bisnis Inovatif, 2026)
The growth of the digital economy in the 5.0 era has changed consumer behavior, particularly among students as digital natives. This study aims to analyze the influence of Celebrity Endorsers, Product Quality, Social Media Marketing, and Influencer Credibility on Purchase Intention, with Brand Image as a mediating variable. The research focuses on students in Pemalang Regency who use the Shopee e-commerce platform. A quantitative approach was employed, with data collected from 100 respondents through purposive and accidental sampling. Data analysis was conducted using multiple linear regression, path analysis, and the Sobel test with IBM SPSS 25. The results indicate that all independent variables have a positive and significant effect on Purchase Intention. In addition, Brand Image is proven to mediate the influence of these variables. The findings suggest that enhancing quality perception and selecting credible endorsers aligned with brand values are important strategies for Shopee to increase consumer purchase intention. This study provides empirical contributions to the development of digital marketing literature.